Strategi Penerapan Metode Project Based Learning untuk Meningkatkan Prestasi Belajar Pada Mata Pelajaran Fiqih di MAN 1 Batam (Prosiding Keislaman dan Sains, 2025)
This research investigates the implementation strategy of Project Based Learning (PBL) in improving students' learning achievement in Fiqh subject at MAN 1 Batam. This research addresses the challenge of conventional teaching methods that often fail to connect Islamic legal theories with students' daily lives. Single case study research with a qualitative approach was conducted over four months (July-October) at MAN 1 Batam. Data collection involved participatory observation of a Fiqh class implementing PBL, semi-structured in-depth interviews with teachers and students, and analysis of learning documents. Data validation used triangulation techniques of sources, methods, and member checking. The implementation of PBL significantly improved students' learning achievement through three main aspects of increasing conceptual understanding through real-world projects such as simulations of buying and selling contracts, developing critical thinking skills in analyzing contemporary Islamic law cases, and improving collaborative problem-solving skills. The research revealed that PBL facilitated a deeper understanding of Fiqh concepts when linked to practical applications. The study is limited by its focus on one institution and relatively short duration. The generalizability of the findings may be limited by the specific context of MAN 1 Batam and students' varying levels of readiness in the implementation of project-based learning. This research provides new insights into the integration of modern pedagogical approaches with Islamic religious education, particularly in Fiqh learning. The research findings contribute to the development of more effective teaching methodologies in Islamic education while maintaining fundamental religious values, as well as offering practical guidance for implementing PBL in religious subjects.
Keywords: Project Based Learing; Islamic Religious Education; Student Learning Achievement